IMPACT OF DIETARY ADDITION OF NETTLE PLANT AS A NATURAL ANTIOXIDANT ON THE PHYSIOLOGICAL PERFORMANCE OF BROILER - Ghadeer A. Rahawi; Wael Younis; Abdullah Abdul-Majeed (Mesopotamia Journal of Agriculture, 2025)
This study was conducted to investigate the nettle plant's physiological effects on the broilers' antioxidant status. At one day of age, 240 chicks (Ross 308) were randomly distributed in three groups (80 birds/group, weighing 40.6±0.3 g each), with four replications for each, and were reared until 42 days of age. The groups were as follows: 1st group (control): received a basal diet without addition; 2nd and 3rd groups: received a basal diet with 2.5 and 5 g nettle/kg diet, respectively. The addition of the nettle resulted in a significant (P≤0.05) increase in total antioxidants at the 5 g/kg diet dose. Similarly, levels of glutathione and glutathione peroxidase increased. On the contrary, the malondialdehyde decreased, and it was significant at the 5 g/kg diet dose, which led to a substantial decrease in corticosterone compared to the control group. Insulin-like growth factor-1 was not significantly affected by adding nettle, while leptin (P≤0.05) decreased significantly compared to the control group. On the other hand, nettle significantly improved the broiler's productivity, especially at the 5 g nettle/kg diet dose, as mean final body weight, total weight gain, and feed consumption significantly (P≤0.05) increased. The feed conversion ratio significantly improved at 42 days of age compared to the control group. We included that the nettle plant can improve the physiological performance and the antioxidant status of broilers and may also reduce oxidative stress, thereby promote growth and improve feed conversion efficiency.